RELIGIOUS FREEDOM IN MARK 9:38-40 AND ITS MISSIOLOGICAL IMPLICATION TO INDONESIAN CONTEXT - Simangunsong, Amran (QUAERENS: Journal of Theology and Christianity Studies, 2024)
Religious freedom is constitutionally guaranteed in Indonesia under Pancasila, yet in practice, violations such as restrictions on places of worship and conflicts involving religious minorities persist. This paradox between legal recognition and practical implementation raises urgent theological and missiological questions. To address this issue, this study interprets Mark 9:38–40, where Jesus’ inclusive teaching challenges exclusivist attitudes and affirms cooperation beyond one’s own community. Using literature study, document analysis, and biblical interpretation, the article explores how this passage provides a theological foundation for an inclusive understanding of mission in Indonesia’s pluralistic context. The findings reveal that Christian mission should transcend institutional boundaries and engage constructively with society through dialogue, respect, and collaboration across faith traditions. Theologically, Mark 9:38–40 affirms that God’s mission operates beyond the visible church, calling Christians to uphold religious freedom as both a constitutional right and a divine mandate. The main contribution of this study lies in integrating Indonesia’s constitutional realities with biblical insights, offering a contextual theological framework that enriches the discourse on religious freedom and strengthens the practice of Christian mission in pluralistic societies.